2015
DOI: 10.1299/mer.14-00298
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on refined theories for beams with applications

Abstract: This paper is a review of the most influential approaches to developing beam models that have been proposed over the last few decades. Essentially, primary attention has been paid to isotropic structures, while a few extensions to composites have been given for the sake of completeness. Classical models -Da Vinci, Euler-Bernoulli and Timoshenko -are described first. All those approaches that are aimed at the improvement of classical theories are then presented by considering the following main techniques: shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 131 publications
0
40
0
1
Order By: Relevance
“…For a comprehensive review about classical and modern 1D modelling techniques, the reader is referred to [34].…”
Section: Classical Beam Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a comprehensive review about classical and modern 1D modelling techniques, the reader is referred to [34].…”
Section: Classical Beam Theoriesmentioning
confidence: 99%
“…Şimşek and Kocatürk [33] studied the free vibration of beams with different boundary conditions within the framework of the third-order shear deformation theory. For further details about modern models for beam structures and a comprehensive review, the reader is referred to [34].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitations of the classical theories and to capture these effects, many enhanced 1D theories of structures have been proposed. A comprehensive review of the most remarkable contributions in the field can be found in Kapania and Raciti 32,33 and in Carrera et al 34 Most of these refined beam models are built based on some physical assumptions, which limit their use to particular classes of problems. In this context, the Carrera Unified Formulation (CUF) 35,36 was presented as a general structural formulation in which the order and the mathematical assumptions of the theory are introduced as input of the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of more complicated problems, such as thin-walled beams subjected to coupling, local effects and other higher-order phenomena, may require the use of evolute and refined beam theories. A comprehensive discussion about higher-order beam models for the linear analysis of metallic structures can be found in the review paper by Carrera et al [30]. Moreover, some detailed expositions of the theories of thin-walled beams before the 1980s can be consulted in the reference texts from Vlasov [31], Bleich [32], Timoshenko and Gere [3] and Murray [33].…”
Section: Introductionmentioning
confidence: 99%